Crystal structure of 4-bromo-3-nitro-1H-pyrazole-5-carboxylic acid dimethyl sulfoxide monosolvate, C4H2N3O4⋅C2H6OS - Radović Ana; Giester Gerald; Tomić Zoran D.; Bigović Miljan; Jaćimović Željko K. (Zeitschrift für Kristallographie - New Crystal Structures)
C4H2N3O4⋅C2H6OS, monoclinic, P21/c (no. 14), a = 6.8751(6) Å, b = 11.0506(10) Å, c = 14.0569(12) Å, β = 97.355(3)°, V = 1059.17(16) Å3, Z = 4, Rgt (F) = 0.0271, wRref (F 2) = 0.0664, T = 200 K.